A Gossip Protocol for Dynamic Resource Management in Large Cloud Environments - SHAMALA A N, DIVYA N, GAYATHRI and MEGHANA D (2014)
INTERNAL GUIDE: Mrs. SHILPA S, MVJCE CD ONLY
Keywords: Dynamic Resource Management in Large Cloud Environments